Pendekatan Edukatif Terhadap Hukuman: Tinjauan Pemikiran Ibnu Al-Qabisi dan Para Ulama - Khotib, M. Umam; Rohati, Siti; Turjiman Ahamd, Lalu; Nur Arifin, Moh (LP3M UNZAH GENGGONG, 2025)
This study aims to explain and analyse educational approaches to punishment in Islamic education based on the thoughts of Ibn al-Qabisi and the views of other scholars. In the context of Islamic education, punishment is not merely understood as a repressive measure, but rather as a pedagogical tool aimed at shaping the character and morality of students. This study employs a literature review method, examining classical and contemporary literature related to the concept of punishment in education. The findings reveal that, according to Ibn al-Qabisi, punishment should be applied wisely, fairly, and proportionally, taking into account the psychological condition and the severity of the student's mistake. A similar approach is also found in the thoughts of several other scholars, who emphasise the educational dimension in the practice of punishment. These findings are relevant for application in contemporary Islamic education systems, particularly in pesantren environments that emphasise the formation of character and moral values. Thus, the concept of educational punishment can serve as a constructive alternative in addressing the challenges of behaviour development among students today.